2017
DOI: 10.1111/liv.13413
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk scoring for predicting non‐alcoholic fatty liver disease in metabolic syndrome patients (NAFLD‐MS score)

Abstract: A simple and non-invasive scoring scheme of five predictors provides good prediction indices for NAFLD in MetS patients. This scheme may help clinicians in order to take further appropriate action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
1
15
0
1
Order By: Relevance
“…Study has shown that NAFLD is closed related to obesity, diabetes, hypertension, hyperlipidemia, and other metabolic syndromes. [ 30 ] Patients with metabolic syndrome have a higher risk of NAFLD in 4 to 11 times than normal people. [ 7 ] Therefore, the American Society of Clinical Endocrinologists lists NAFLD as one of the components of metabolic syndrome in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Study has shown that NAFLD is closed related to obesity, diabetes, hypertension, hyperlipidemia, and other metabolic syndromes. [ 30 ] Patients with metabolic syndrome have a higher risk of NAFLD in 4 to 11 times than normal people. [ 7 ] Therefore, the American Society of Clinical Endocrinologists lists NAFLD as one of the components of metabolic syndrome in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, MRI-PDFF had been used to diagnose the hepatic steatosis in several countries and the reliable accuracy, sensitivity and specificity had been verified [14,15,25,29]. Besides the imaging and pathological diagnosis, some molecular prediction models based on the clinical parameters, genetics information, and serum biochemical factors had been constructed for the prediction of the risk of NAFLD frequently [30][31][32], but the sensitivity and specificity of them were remain worth discussed based on the most accurate NAFLD diagnostic method such as MRI-PDFF in different ethnics and regions. In this study, we performed the MRI-PDFF examination as the NAFLD diagnostic gold standard to verify the diagnostic value of NAFLD molecular prediction model FLI, NAFLD LFS and Liver fat (%) in Chinese Han population that had been reported previously [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In order to build our proposed predictive model, we have exploited the capabilities of logistic regression. As the general formula of logistic regression in terms of sigmoid function can be expressed as follows [19]:…”
Section: The Framework Of the Predictive Modelmentioning
confidence: 99%